2021
DOI: 10.1021/acs.inorgchem.1c02136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pairwise Reactions on the Synthesis of Li0.3La0.57TiO3 and the Resulting Structure–Property Correlations

Abstract: The performance of single-ion conductors is highly sensitive to the material’s defect chemistry. Tuning these defects is limited for solid-state reactions as they occur at particle–particle interfaces, which provide a complex evolving energy landscape for atomic rearrangement and product formation. In this report, we investigate the (1) order of addition and (2) lithium precursor decomposition temperature and their effect on the synthesis and grain boundary conductivity of the perovskite lithium lanthanum tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…21 The observation that a high synthesis temperature is necessary is also in agreement with previously reported syntheses, which all utilized temperatures > 1200 °C. 21,22,24,25,27,29,30,32,33,61 The different precursors have led to the formation of polymorphs. This result is unusual as at the synthesis temperature of 1300 °C, LLTO should be present in the cubic Pm-3m polymorph, 21 yet as the sample cools with the same cooling conditions (5 °C min −1 ), different polymorphs are stabilized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The observation that a high synthesis temperature is necessary is also in agreement with previously reported syntheses, which all utilized temperatures > 1200 °C. 21,22,24,25,27,29,30,32,33,61 The different precursors have led to the formation of polymorphs. This result is unusual as at the synthesis temperature of 1300 °C, LLTO should be present in the cubic Pm-3m polymorph, 21 yet as the sample cools with the same cooling conditions (5 °C min −1 ), different polymorphs are stabilized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 The double-perovskite P4/mmm structure has also been reported at room temperature. 30,32 The P4/nbm structure transforms into the double perovskite (before ultimately transforming to Pm-3m), whereas the I4/mcm structure transitions into the PC structure. These results indicate that the synthesis conditions are highly important to the structure.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxide electrolytes can generally divided into garnet-type Li 7 La 3 Zr 2 O 12 (LLZO), NASICON-type LiTi 2 (PO 4 ) 3 , LiSICONtype Li 14 Zn(GeO 4 ) 4 , and Perovskite-type La 0.5 Li 0.5 -dTiO 3 (LLTO). [15,[97][98][99] Due to the large rigidity of the oxide electrolyte, many methods have been employed to fabricate relatively dense and well-contacted oxide mixtures. Qin et al introduced nano La 2 O 3 as an effective additive to promote the uniform distribution of Li 6.5 La 3 Zr1.5Ta 0.5 O 12 particles, as well as to construct a 3D lithium-ion transport network along the grain boundary.…”
Section: Heat Treating Of Oxide Solid Electrolytementioning
confidence: 99%
“…Perovskite-type lithium lanthanum titanate Li 0.5 La 0.5 TiO 3 (LLTO) and structurally related sodium lanthanum titanate Na 0.5 La 0.5 TiO 3 (NLTO) are being studied as potential solid electrolytes for solid-state batteries, which would be advantageous in terms of safety compared to batteries based on liquid electrolytes. It was found that LLTO is much more promising than NLTO for its similar structure with space group P 4/ mmm . Lanthanum ions are a main contribution for the stabilization of the crystalline structure, while lithium ions are the charge carriers, and the La layers can block the diffusion of the mobile ions.…”
Section: Introductionmentioning
confidence: 99%